Experimental and finite element analysis of solvent cast poly (lactic acid) thin film blends - Syed Shaharuddin, Sharifah Imihezri; Mukhtar, Abdul Rahman; Mohd. Akhir, Nur Atiqah; Shaffiar, Norhashimah; Othman, Maizatulnisa (IIUM Journal Publication Unit, 2019)
A combined experimental and finite element analysis (FEA) investigation was performed to study the effect of incorporating poly(propylene carbonate)(PPC) and curcumin on the mechanical properties of poly(lactic acid) (PLA). In addition, the chemical interaction and morphological changes brought upon by each subsequent additive were also observed. The addition of PPC at 30 wt% into PLA causes a decrease in strength and modulus by 51% and 68% respectively whilst inducing higher elongation by 74%. The resultant decrease in strength and modulus of the PLA/PPC blend was recovered by adding a low weight percentage (1 wt%) of curcumin. The images of the fractured surfaces via scanning electron microscope (SEM) revealed the brittle-ductile-brittle progression of PLA due to the addition of PPC and curcumin which corroborates the findings from the tensile test. Fourier-transform infrared spectroscopy (FTIR) revealed that the addition of PPC by 30 wt % resulted in chemical interaction between the carbonyl groups of PLA and PPC as the C=O peak of PLA slightly shifted to a lower wavenumber. The presence of curcumin peaks however was found to be difficult to be identified in the PLA/PPC/curcumin blend. The simulated results for the stress-strain profile using FEA agreed well with the experimental tensile test profile with a relatively low percentage error of less than 6%. Therefore, it was concluded that for these compositions, the developed model can be used for further simulation works to design biomedical devices.